Determinação de micotoxinas por UPLC-MS/MS em grãos armazenados sob condições de temperatura e atmosfera controlada - Nunes, Maria da Graça Pereira (2019)
This work aimed to develop and validate analytical methods for the determination of mycotoxins in beans, corn and soybean using UPLC-MS/MS and to evaluate the occurrence of mycotoxins in samples of these grains after six months of storage under controlled atmosphere. The extraction of mycotoxins was performed using the QuEChERS method, which was optimized so that the highest number of mycotoxins were extracted with recoveries between 70 and 120% and RSD ≤ 20%. Subsequently, the optimized methods were validated for beans and soybeans based on three guidance documents. Samples (5 g) were extracted with 10 mL of acetonitrile containing 1% formic acid for beans and maize, and 5% formic acid for soybean, followed by partitioning with MgSO4 and diluting the extract 1: 1 (v / v) with methanol directly into vial. Samples submitted to 15 controlled atmosphere treatments for four bean cultivars (Fepagro 26, Garapia, Cowpea white and red beans), four soybean cultivars (Brasmax Ultra IPRO, Brasmax Desafio RR, Brasmax Bonus IPRO and Tec IRGA 6070) were analyzed and 6 treatments for maize. Treatments were carried out at three temperature (20, 25 and 30 ºC) and at atmosphere with control of the partial pressures of O2 and CO2. There was no occurrence of mycotoxins in the cultivars Cowpea white and red beans, and soybean cultivars Brasmax Desafio RR and Brasmax Ultra IPRO. Aflatoxin B1 (AF B1) was detected in the other bean and soybean cultivars. For the cultivars Fepagro 26 and Garapia, no mycotoxins were detected in the grains stored at temperatures ≤ 20 ºC. For the cultivars Brasmax Bonus IPRO and Tec IRGA, AF B1 was detected in all the studied samples, indicating that the storage conditions were not effective to prevent the contamination of the samples. AF B1, fumonisins B1 and B2 (FM B1 and FM B2, respectively) were detected in all maize samples, although FM B1 was not detected in grain stored with moisture content at 14% at 30 ºC and ambient atmosphere.